CLINICO-PHYSIOLOGIC SIGNIFICANCE OF HEART RATE VARIABILITY IN CHRONIC ISCHEMIC HEART DISEASE - Zemaityte, D. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The paper represents of the results of analysis of heart rate variability (HRV) in patients with chronic ischemic heart disease (IHD) in the context of search for informative characteristics for prognoses of IHD development and its end-points based on data of 297 healthy subjects and 4561 IHD patients (pts) (range of age was 20-84yr’s). HRV was analyzed by means of calculation of HR power spectrum, HR responses to complex of tests (active orthostatic test, bicycle ergometry, night sleep), non-linear dynamics analysis methodology and baroreflex sensitivity. There was shown, that the pattern of HRV depend on level of development of IHD and its complications or leading pathology, having an impact to HR parameters due changes of mechanism and particular point of influence to HR autonomic control. The level of impact depends of the changes in cardiovascular functional state, particularly of development of congestive heart failure. HRV changes were dependent on increase of an impact of humoral-metabolic HR control due to depression of nervous reflex control, particularly parasympathetic one. Because of that, changes of HRV in IHD pts enable to follow the tendencies of development and treatment efficacy. As it was shown for myocardial infarction, in chronic IHD pts, there were possibility to use HRV characteristics, reflecting parasympathetic control, for cardiac death prognoses.